HYBRID COURT SEBAGAI ALTERNATIF PENYELESAIAN PELANGGARAN HAK ASASI MANUSIA - Cholidah Cholidah (Legality : Jurnal Ilmiah Hukum, 2018)
The establishment of the International Criminal Court (ICC) in 1998 provided a hope for certainty in resolving cases of international human rights crimes that occurred after the Rome Statute which formed the basis of this court ratification in 1998, the Non-Retroactive Principles adopted in the Rome Statute did not open this courtroom Human rights crimes that occurred before 1998, so that a new court model is needed to resolve human rights cases that occur namely the Hybrid Court Judicial model, also known as the Mixed Court model, seeks to combine national legal and judicial elements with the International. This Alternative Model is then chosen in resolving cases of human rights crimes that occurred in Sierra Leone and Cambodia, but given the different human rights crimes that occur, different approaches and models are needed in the formation of selected Hybrid Court Courts. So it needs to be explored about the urgency, the legal status of Hybrid Court formation, as well as the technical mechanisms of the trial, both Special Court for Sierra Leone and Extra Chamber Court of Cambodian/ECCC. The results of this study are first, the urgency of the formation of Hybrid Court is to fill the limitations of temporis jurisdiction from the ICC as an institution in prosecuting perpetrators of international crimes so as to close the impunity of perpetrators because the State can still try its citizens by using its domestic legal system without having to fully use the International mechanism. Second, Hybrid Court can be formed through agreements between the United Nations and the government of a country which is then used as a legal basis for the court, as implemented in Cambodia, besides that the formation of Hybrid Court can also be formed through national laws as applied in Sierra Leone.